2019
DOI: 10.1002/eat.23128
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal follow‐up of a comprehensive operationalization of eating disorder recovery: Concurrent and predictive validity

Abstract: Objective We aimed to replicate the concurrent validity of a comprehensive definition of eating disorder recovery (physical, behavioral, and cognitive indices) in a sample followed up 7–8 years from baseline, and to examine, for the first time with this comprehensive definition, predictive validity. Method Participants were 66 women with a history of an eating disorder and 31 age‐matched controls who completed an online survey and phone interview. Results In general, women who were fully recovered were statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Psychiatric recovery can be difficult to operationalize [29], and remains in a developing stage in the field of AN [30,31]. While many patients with AN can reach an extended period of considerable improvement, many still experience long-term residual symptoms [30,[32][33][34].…”
Section: Model Design and Structurementioning
confidence: 99%
“…Psychiatric recovery can be difficult to operationalize [29], and remains in a developing stage in the field of AN [30,31]. While many patients with AN can reach an extended period of considerable improvement, many still experience long-term residual symptoms [30,[32][33][34].…”
Section: Model Design and Structurementioning
confidence: 99%
“…Subsequent studies have reported a similar pattern of results on measures of perfectionism, self-concept, coping, negative affect, negative urgency, eating expectancies, objectified body consciousness, motivation for exercise, and body appreciation and intuitive eating [ 23 31 ]. There is also preliminary evidence that this definition is valid among men [ 32 ] and predictive of sustained ‘full recovery’ status as defined by the Bardone-Cone definition [ 33 ]. It is important to note however, that all of these studies except for Bardone-Cone et al [ 32 ] were conducted in the same sample of women recruited from a child and adolescent treatment program, calling into question the generalizability of this model.…”
Section: Introductionmentioning
confidence: 99%
“…This pilot study considers whether the Bardone‐Cone et al criteria identify a recovered group among men with a history of an eating disorder. These criteria were selected because they have demonstrated concurrent validity, albeit in women (Bardone‐Cone et al, ), and have initial support for predictive validity (Bardone‐Cone et al, ), with full recovery (physical, behavioral, and cognitive recovery criteria) at baseline predicting meeting criteria for full recovery 7–8 years later. Furthermore, initial research comparing comprehensive definitions of recovery proposed by Pike (), Kordy et al (), and Bardone‐Cone et al () concluded with the recommendation to adopt the Bardone‐Cone et al criteria in assessing recovery (Ackard, Richter, Egan, & Cronemeyer, ).…”
Section: Introductionmentioning
confidence: 99%